Ready to Read : A Dozen Dizzy Dogs - Hooks, William H.; Baseman, Gary (Milwaukee, Wis. : Gareth Stevens Publishing, 1997)
A dozen dizzy dogs have an adventure with a bone.
K-3
Keywords: Dogs -- Fiction; Counting -- Juvenile literature; Early chapter